Comprehensive assessment of the quality of life in heart transplant recipients: experience at Shumakov National Medical Research Center of Transplantology and Artificial Organs - I. I. Muminov; A. A. Yusova; N. N. Koloskova; A. O. Shevchenko; R. Yu. Bangarov; M. S. Nesterova (Вестник трансплантологии и искусственных органов, 2025)
Heart transplant (HT) is an effective treatment option for patients with end-stage chronic heart failure, as it can restore their ability to work, facilitate physical and social rehabilitation, and significantly improve their long-term survival. Objective: to evaluate the psychological and physical well-being of HT recipients using a comparative analysis of the TxEQ, PTGI, and SF‑36 questionnaires and the impact of the obtained results on the frequency of visits to health care facilities. Materials and methods. The findings of the study were derived by analyzing the data of recipients by random randomization, who were observed on an outpatient basis at Shumakov National Medical Research Center of Transplantology and Artificial Organs. The TxEQ, SF‑36, and PTGI questionnaires were used to assess recipients’ psychological and physical well-being. For comparative analysis, HT recipients were divided into three equal groups based on the total score obtained when assessing each factor in the TxEQ questionnaire. Results. A comparative evaluation of factors from the TxEQ questionnaire and scores from the SF‑36 questionnaire revealed that recipients who scored poorly on a particular factor had better mental health (p = 0.02). Recipients who are more eager to inform others about their surgery show better vitality (p = 0.019). Analysis of the «Medication adherence» factor found that there was a significantly high compliance of recipients to taking their medications (p = 0.01). Subsequent data analysis showed that the total PTGI score strongly correlated with the factors «Responsibility», «New life perspectives», «Disclosure» and «Medication adherence» (p < 0.005). While analyzing factors from the TxEQ questionnaire and the frequency of recipients’ outpatient visits to health care facilities, it was revealed that recipients who were more worried about their surgery and those who exhibited high medication adherence during the follow-up year visited health care facilities more often (p < 0.005). Conclusion. Regularly assessing the quality of life in HT recipients is a key factor of outpatient followup, which allows to significantly improve physical and psychological well-being, and ultimately preventing the risk of negative health complications.